Dark Energy Survey Year 3 results: redshift calibration of the MagLim lens sample from the combination of SOMPZ and clustering and its impact on cosmology - Giannini, G.; Alarcon, A.; Gatti, M.; Porredon, A.; Crocce, M.; Bernstein, G. M.; Cawthon, R.; Sánchez, C.; Doux, C.; Elvin-Poole, J.; Raveri, M.; Myles, J.; et al. (Oxford University Press (OUP), 2024)
We present an alternative calibration of the MagLim lens sample redshift distributions from the Dark Energy Survey (DES) first 3 yr of data (Y3). The new calibration is based on a combination of a self-organizing-map-based scheme and clustering redshifts to estimate redshift distributions and inherent uncertainties, which is expected to be more accurate than the original DES Y3 redshift calibration of the lens sample. We describe in detail the methodology, and validate it on simulations and discuss the main effects dominating our error budget. The new calibration is in fair agreement with the fiducial DES Y3 n(z) calibration, with only mild differences (<3σ) in the means and widths of the distributions. We study the impact of this new calibration on cosmological constraints, analysing DES Y3 galaxy clustering and galaxy-galaxy lensing measurements, assuming a Lambda cold dark matter cosmology. We obtain
Keywords: dark energy; galaxies: distances and redshifts; gravitational lensing: weak